Orthopedic protraction maxillary in retrognathism of fissured and nonfissured patients in comparison with ecuadorian norm, 2013 - Terreros de Huc, María Angélica (Revista Universidad de Guayaquil, 2014)
The effectiveness of maxilla protraction of the facial mask prior to palatal expansion was evaluated in both fissured and non-fissured palate patients , Class III skeletal relationship ,in proportion to the Ecuadorian Universe Standard 81 H. C. FUNARMAF,sampling through cephalometric analysis: 21 H. C. fissured patients (26 % ), (15m, 6f ), average age:12 11mths, and 7 H. C. non-fissured (9 % ), (3m,4f) average age: 11 consists of 35% of the universe, temporary teeth, mixed and young permanent teeth . 19 Angular measures and 12 linear measures were compared pre post-treatment; postreatment average Ecuadorian standard (9m: 21f), Class I dental and skeletal relationship, average age 16 2mths. Average treatment time 16mths fissured; 20ms non-fissured; Statistical test: t Test pairs. Treatment develops significant trend of growth time (p < 0.05 ) with severe mandibular rotation, maxillary increase in height and lower facial height exceeding standard average, severe dolicofacial pattern , more accentuated in fissured patients , maxillary advance and normal intermaxillary relationship; improvement in protrusion and inclination upper and lower incisors, overjet and overbite without reaching fissured group; little significant difference with the standard group non-fissured, with the exception of retroclinacion of lower incisors. Lower lip exceeds standard significantly in fissured group, affecting facial profile.